Bilateral synchronous tonsillar metastasis from a mixed form of neuroendocrine tumor in the lung: Case report and literature review. Issue 12 (26th October 2020) - Noël, Antoine; Rodriguez, Alexandra; Lelong, Clément; Noël, Jean‐Christophe
Abstract : Here, we report the case of a 54‐year‐old man with a history of squamous cell carcinoma (SCC) of the lung, who developed bilateral neuroendocrine carcinoma (NEC) of the palatine tonsils. Faced with this atypical situation, another biopsy of the lung lesion was performed, revealing NEC histology patterns. This article describes the first case of metastasis to the bilateral palatine tonsils from the NEC component of a mixed NEC/SCC of the lung, highlighting the importance of reconsidering the diagnosis of the primary tumor histology, particularly in lung cancer with the possible presence of mixed tumor after phenotype transdifferentiation of the primary tumor. Key points: Significant findings of the study: Mixed lung carcinoma can be revealed after the presence of neuroendocrine carcinoma metastasis. What this study adds: Bilateral neuroendocrine carcinoma of the palatine tonsils should be considered as metastases, particularly in the presence of lung cancer with a poor response to treatment. Abstract : Mixed lung carcinoma can be revealed after the presence of neuroendocrine carcinoma metastasis.Bilateral neuroendocrine carcinoma of the palatine tonsils should be considered as metastases, particularly in the presence of lung cancer with a poor response to treatment.